Sikap Non Muslim terhadap Adzan di Kampung Sawah Kecamatan Besting Kabupaten Langkat - Prayoga, Muhammad; Zulkarnaen, Zulkarnaen; Munandar, Munandar (Lembaga Yasin AlSys, 2023)
In general, this research aims to find out: how the Muslim community perceives the sound of the call to prayer in Sawah village, Besitang sub-district, Langkat district and to find out how the Christian community perceives the sound of the call to prayer in Sawah village, Besitang sub-district, Langkat district. This type of research is descriptive qualitative research, namely the data collected is in the form of words, images, not numbers. In this case the researcher classifies sources into two categories, namely primary sources and secondary sources and the researcher collects data by means of observation, interviews and documentation. The results of this research show that the Islamic community views the Adhan as a notification that the time for prayer has arrived with the lafadz that has been determined by the syara of the adhan lafadz, namely Hayya alash shalah which means let's go to prayer and Hayya alal falah which means let's go to victory or happiness, from the adhan lafadz It is clear that the call to prayer is included in da'wah, namely inviting all mankind to pray so that life can be happy in this world and the hereafter. The Christian community views the sound of the call to prayer. Meanwhile, the view of the Christian community is that initially, they admit that the call to prayer can interfere with some of their activities such as working or interacting with friends outside the home. However, as time passes, this individual experiences a transformation in mindset and reaches a deep understanding of the cultural and religious values associated with the call to prayer, as well as accepting its importance for his community.